Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

need help with this problem ​

Need Help With This Problem class=

Sagot :

Answer:

 h(x) =  -x² + 11 x + 2

Step-by-step explanation:

Explanation:-

Given that the functions are  

                                            f(x) = 2 x² - 5x -3

                                            g(x) = x² + 6x -1

               h(x)  = g(x) - f(x)

                      = x² + 6x -1 - (2 x² - 5x -3)

                     = - x² + 6 x +5x -1+3

                    = -x² + 11 x + 2

            h(x) =  -x² + 11 x + 2

Final answer:-

h(x) =  -x² + 11 x + 2